2005
DOI: 10.1200/jco.2005.07.166
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Nanoparticle-Enhanced Magnetic Resonance Imaging in the Diagnosis of Lymph Node Metastases in Patients With Endometrial and Cervical Cancer

Abstract: Lymph node characterization with USPIO increases the sensitivity of MRI in the prediction of lymph node metastases, with no loss of specificity. This may greatly improve preoperative treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
149
1
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(163 citation statements)
references
References 22 publications
4
149
1
9
Order By: Relevance
“…Pathologic examination did not reveal any particular feature except for a discrete capsular thickening but devoid of metastasis. This suggests that this pattern of nodal enhancement should also be viewed as a pattern variant for normal enhancement and not as a sign of metastatic involvement, as it was previously pointed out by Rockall et al (30) when evaluating pelvic lymph nodes in patients with gynecological cancers. Inflammatory nodes can also show a reduced uptake of USPIO due to hyperplasia of the germinal centers and paucity in macrophages as occurred in one of our cases.…”
Section: Discussionmentioning
confidence: 54%
“…Pathologic examination did not reveal any particular feature except for a discrete capsular thickening but devoid of metastasis. This suggests that this pattern of nodal enhancement should also be viewed as a pattern variant for normal enhancement and not as a sign of metastatic involvement, as it was previously pointed out by Rockall et al (30) when evaluating pelvic lymph nodes in patients with gynecological cancers. Inflammatory nodes can also show a reduced uptake of USPIO due to hyperplasia of the germinal centers and paucity in macrophages as occurred in one of our cases.…”
Section: Discussionmentioning
confidence: 54%
“…They are also promising in comparison to other blood derived biomarkers like Ca 125, imaging methods and clinicopathological risk factors which were reported to predict more advanced disease. [51][52][53] In conclusion, our study revealed that a set of miRNAs was regulated in tissues and plasma of EEC patients. We confirmed expression alterations of several miRNAs that were previously indicated in EEC, which helps to establish a miRNA panel characteristic for this malignancy.…”
Section: Early Detection and Diagnosismentioning
confidence: 99%
“…As discussed earlier, CT and conventional MRI have limited accuracy in detecting recurrent nodal disease, and although contrast-enhanced MRI with lymphotropic superparamagnetic nanoparticles appears promising for the detection of lymph node metastases, it has not received regulatory approved in the United States (107). As an alternative to CT or MRI, immunoscintigraphy with capromab is controversial.…”
Section: Post-treatment Detection Of Metastasesmentioning
confidence: 99%